(untitled) - Zeynab Baghaei (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
This study was conducted to investigate the effect of the readability of the board report on the risk of stock price falls in companies listed on the Tehran Stock Exchange. In terms of purpose, this research is applied and descriptive-correlation in terms of nature. Hundred twenty companies were considered for analysis to achieve the research goal. These companies were among the companies listed on the Tehran Stock Exchange from 2013 to 2018 by systematic screening method and a total of 720 years-companies. The multivariate regression model and the ordinary least squares method were used to test the research hypothesis. There is a negative and significant relationship between the readability of the board report and the risk of falling stock prices based on the findings.